EXPERT SYSTEM DIAGNOSE DISEASES IN GOATS USING THE APPLICATION OF CERTAINTY FACTOR AT THE ASAHAN DISTRICK LIVESTOCK SERVICE - Lizza Nattasya Marpaung; Dahriansah; Cecep Maulana (Informatika, Universitas Jenderal Soedirman, 2022)
Goats are livestock that provides many benefits for humans such as meat, milk, and skin. Goat meat is now also one of the important foodstuffs in meeting people's nutrition and is widely marketed. Livestock health is the most important factor in the cultivation of goats, therefore the presence of diseases in goats can result in economic losses because it can reduce livestock productivity and can even cause death in goats. However, most of the goat breeders still lack knowledge of disease control in goats plus the ratio of the number of experts is not balanced with the number of breeders which causes limited service facilities for a consultation so that it is increasingly difficult for breeders to identify the type of disease early on and the solutions that will be carried out next. To overcome this problem, an expert system was built that can assist farmers in diagnosing diseases in goats. This study uses the certainty factor method in solving problems that exist in goats. The data used in this study consisted of 8 disease data and 30 symptom data caused by bacteria, viruses and parasites. Each symptom has a CF value given by experts, namely veterinarians. So that a 90% percentage of the level of conformity for the system's accuracy level is obtained based on the results of expert and system validation.